Characterization and Comparative Analysis of Complete Chloroplast Genomes of Three Species From the Genus Astragalus (Leguminosae) - Tian, Chunyu; Li, Xiansong; Wu, Zinian; Li, Zhiyong; Hou, Xiangyang; Li, Frank Yonghong (Frontiers in Genetics, 2021)
Astragalus is the largest genus in Leguminosae. Several molecular studies have investigated the potential adulterants of the species within this genus; nonetheless, the evolutionary relationships among these species remain unclear. Herein, we sequenced and annotated the complete chloroplast genomes of three Astragalus species—A. adsurgens, A. mongholicus var. dahuricus, and A. melilotoides using next generation sequencing technology and plastid genome annotator（PGA） tool. All species belonged to the inverted repeat lacking clade (IRLC), and had similar sequences concerning gene contents and characteristics. Abundant simple sequence repeat (SSR) loci were detected, with single nucleotide repeats accounting for the highest proportion of SSRs, most of which were A/T homopolymers. Using A. membranaceus var. membranaceus as reference, the divergence was evident in most non-coding regions of the complete chloroplast genomes of these species. Seven genes (atpB, psbD, rpoB, rpoC1, trnV, rrn16, and rrn23) showed high nucleotide variability (Pi), and could be used as DNA barcodes for Astragalus sp. cemA and rpl33 were found undergoing positive selection by the section patterns in the coded protein. Phylogenetic analysis showed that Astragalus is a monophyletic group closely related to the genus Oxytropis within the tribe Galegeae. The newly sequenced chloroplast genomes provide insight into the unresolved evolutionary relationships within Astragalus spp. and are expected to contribute to species identification.